Eradication of Histopathological and biochemical changes in testes and reproductive organs on Exposure to organophosphate, ethion - Y. KRISHNAPUR, SUVARNARAJESH. (Technium BioChemMed, 2020)
Ethion an organophosphate was orally administrated at16mg/kg/day to Swiss albino mice for 5, 10, and 20 and 30 days, control mice received similar quantities of olive oil. Daily body weight was recording and was recorded. The mice were sacrificed by cervical dislocation after 24 hours after terminal exposure of ethion, in the number of spermatogonia, diameter of spermatocyte and spermatids in 20 days and number of spermatids 10 days ethion treated mice, the histological studies of the testis of the mice treated with ethion for long durational revealed spermatogenesis inhibition reflected by significantly decreases in the number of spermatogial cell and sperms, when compared with controls, in the mice treated with ethion for 20 and 30 days showed significantly decreases in the weight of the prostate gland, however increases in significantly in 30 days however weight of Cowper’s gland decreased in significantly in 30 days ethion treated mice . there was significantly increased testis at the dose of 20, 30,significantly increase and decrease in the epididymis, cowpe’s gland and liver weight., whereas adrenal weight increases significantly in mice treated with ethion for30 days, however kidney adrenal and liver weight significantly in mice treated with ethion for 30 days however adrenal weight increased significantly in the treated with ethion for 10,20, and 30 days in mice treated with ethion for 20 days caused significant decrease in the level of DNA significant in the level of proteins and significantly increases in the level of glycogen and cholesterol in the testis, however, was significantly decreases in level of liver glycogen and DNA in liver.in mice treated with ethion for 30days caused significantly decrease in Glycogen and DNA in liver, these observed effect of ethion on testis and biochemical Constituents may be due to hormonal imbalance in the stages in the hyphalamohypophysial- Testicular axis